Chinese philosophy as a world philosophy - Li, Chenyang (2023)
I will argue for three points. The first is on the need to make Chinese philosophy a world philosophy. The second point is that, in order to promote Chinese philosophy as a world philosophy we should not historicize philosophy. Philosophy and history are two different disciplines. As important as historical context is, overemphasizing it or even taking philosophy merely as a matter of intellectual history makes it difficult for non-specialists to study Chinese philosophy, and is therefore counter-productive to advancing it as a world philosophy. A good balance is thus needed in order to develop Chinese philosophy in response to contemporary needs and not to exclude a large number of non-specialists from studying and drawing on it. My third point is that comparative philosophy is the most effective way to study, examine and develop Chinese philosophy as a world philosophy. Comparative philosophy provides a much needed bridge across different cultures for philosophy to connect on the world stage.